2014
DOI: 10.1007/s13765-014-4162-5
|View full text |Cite|
|
Sign up to set email alerts
|

Classification of Korean Chrysanthemum species based on volatile compounds using cluster analysis and principal component analysis

Abstract: In the analysis of chemotype relationship among Korean Chrysanthemum species, the volatile compounds in the leaves of 15 taxa were analyzed and identified by gas chromatograph/mass spectrometry. Principal component analysis and cluster analysis used for the grouping based on the volatile compounds. Fifteen taxa of Charysanthemum species were categorized into three groups. Groups I and II included higher ketones than Group III. Group I had five C. zawadskii subspecies: acutilobum, acutilobum var. tenuisectum, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The findings on the content of VOCs and other secondary metabolites in Chinese chrysanthemum flowers revealed 58 volatile compounds (Sun et al, 2010). Kim et al (2014) analyzed the volatile compounds extracted from leaves from fifteen taxa of Korean Chrysanthemum species. With the chemotypes received, they were able to classify the taxa tested into three groups, different in terms of the quantity of particular secondary compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The findings on the content of VOCs and other secondary metabolites in Chinese chrysanthemum flowers revealed 58 volatile compounds (Sun et al, 2010). Kim et al (2014) analyzed the volatile compounds extracted from leaves from fifteen taxa of Korean Chrysanthemum species. With the chemotypes received, they were able to classify the taxa tested into three groups, different in terms of the quantity of particular secondary compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The HuaiJu teas exhibited the highest total content of volatile components (2671.13 μg g −1 ), followed by XueJu (2014.66 μg g −1 ), BoJu (1957.01 μg g −1 ), HangJu (1742.57 μg g −1 ) and FuJu (1742.48 μg g −1 ). The differences revealed that the volatile components of chrysanthemum flower teas were affected by their origins (Kim et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Scores and loadings identified the correlation between sample classification and aroma notes (aroma‐active components) (Kim et al ., ; Yao et al ., ). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Anthocyanins from blueberries prevented A2E-induced cytotoxicity by reducing A2E-epoxidation. Some volatile compounds, including camphor, borneol, α-pinene, camphene, 1,8-cineole, germacrene-D, α-thujene, α-muurolene, piperitol, and hinesol, were identified in the essential oils of the CB flowers [52,53]. The essential oil of CB flowers is usually extracted by steam distillation, which vaporizes water and is obtained by redissolving it in an organic solvent.…”
Section: Discussionmentioning
confidence: 99%